Assessing Mothers’ Parenting Stress: Differences Between One- and Two-Child Families in China - Qian, Guoying; Mei, Jin; Tian, Li; Dou, Gang (Frontiers in Psychology, 2021)
This study aims to investigate mothers’ parenting stress, and explore the relationship between mothers’ parenting stress in two-child families, involving preschool children, and the associated demographic variables. A sample of 621 two-child families and a comparison group of 319 one-child families from China participated in the study; the children were aged between 3-7. The results indicated the following: (1) Compared with one-child mothers, parenting stress in two-child mothers was higher. (2) In two-child families, birth order, gender combination, and the age gap between siblings were found to have significant impacts on maternal parenting stress. (3) With regard to two-child families, maternal parenting stress in in families with an income of less than 3,000 yuan were significantly higher than that of mothers in families with an income of more than 6,000 yuan.